McKinseyisierung oder Regierungsprojekt? Unternehmensberatungen in der strategischen Stadtentwicklung. Das Beispiel „Metropole Hamburg – Wachsende Stadt“ - Vogelpohl, Anne (Raumforschung und Raumordnung | Spatial Research and Planning, 2017)
At the beginning of the millennium, Hamburg’s urban strategy “Metropolis Hamburg – Growing City” was a sensation for urban studies and urban planning. On one hand, it was one of the first urban policy papers that explicitly focused on growth, on the other hand, entirely new actor constellations within urban development became apparent because external experts like management consultants were identified as key actor besides urban government and planning department. This was generalized as “McKinseyization“. Taking Hamburg as an example, this paper addresses the questions which role the consultancy McKinsey played for the Growing City Strategy and what McKinseyization of urban development means against this background. These questions are still highly relevant because management consultants are regularly involved in urban and regional development strategies ever since then. In order to bind these diverse topics together, I begin with introducing the interrelationships between strategic urban development and consulting. Then I will elaborate the concrete interrelationship between Hamburg’s strategy and McKinsey’s paper “Hamburg Vision 2020” from 2001. The analysis shows that the thesis of a McKinseyization needs to be re-evaluated: from a direct influence of McKinsey towards the production of a context which enables the establishment of new entrepreneurial urban policies. Finally I qualify the dimensions characterizing a McKinseyization. The paper thus contributes to a still pending processing of the Growing City strategy‘s roots and generally synthesizes the complex context of origin of strategic urban development under the influence of external advice.
Keywords: Urban development strategies; Expertise; McKinsey; Consulting; Urban policy; Hamburg